2019
DOI: 10.1177/0333102419876920
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive vagus nerve stimulation (nVNS) for the preventive treatment of episodic migraine: The multicentre, double-blind, randomised, sham-controlled PREMIUM trial

Abstract: Introduction Non-invasive vagus nerve stimulation (nVNS; gammaCore®) has the potential to prevent migraine days in patients with migraine on the basis of mechanistic rationale and pilot clinical data. Methods This multicentre study included a 4-week run-in period, a 12-week double-blind period of randomised treatment with nVNS or sham, and a 24-week open-label period of nVNS. Patients were to administer two 120-second stimulations bilaterally to the neck three times daily (6–8 hours apart). Results Of 477 enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 33 publications
2
61
1
3
Order By: Relevance
“…In comparison, rPMS led to a clearer decrease depending on the stimulated muscle, which probably points to a considerably higher improvement in the QoL. In this context, the side effects of rPMS tend to be less severe than those reported for VNS and SONS and, consequently, might result in higher acceptance of rPMS and better satisfaction 39,43,45 .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In comparison, rPMS led to a clearer decrease depending on the stimulated muscle, which probably points to a considerably higher improvement in the QoL. In this context, the side effects of rPMS tend to be less severe than those reported for VNS and SONS and, consequently, might result in higher acceptance of rPMS and better satisfaction 39,43,45 .…”
Section: Discussionmentioning
confidence: 90%
“…Despite these promising first results focusing on the peripheral part of the TCC, further insights into rPMS and its central effects for intervention in migraine are lacking. Comparing rPMS to the latest investigations of other available neuromodulative techniques for intervention in migraine, the reduction of migraine attacks and days suffering from headache are generally in a comparable range 33,36,39,43 . In the ESPOUSE study, single-pulse TMS was applied to the occiput by the study participants twice a day during three months as a prophylactic treatment and also as an acute intervention during any migraine attack occurring in this period of time 33 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also important to note that the present definition did not consider failure to devices or nonpharmacological therapies. A number of studies have shown that vagal nerve stimulation, biofeedback, relaxation, and cognitive behavior therapy are as efficacious for migraine as placebo, but still better than no improvement [54,55]. However, behavioral treatments are less accessible, more professional-dependent and less standardized than pharmacological treatments, and in certain countries, not reimbursed by the Healthcare systems, than pharmacological treatments.…”
Section: Other Limitations To the Definitionmentioning
confidence: 99%